Meaning of life in initial teacher training: paths towards meeting it - Chan Chi, Gladis Ivette (2024)
The meaning of life has been widely explored in areas such psychology, but less addressed in teaching training. The aim of this research is to describe the pathways that support the connection between the meaning of life and their contribution in aid of initial teaching training from a public university stablished in Southern Mexico. The methodology was qualitative, exploratory and interpretive. The obtained data were analyzed based on content analysis technique. Four categories were stablished: 1) Self-knowledge, 2) Mission as a resource for meaning, 3) Meaning-oriented goals, and 4) Difficulties as a guidance to meaning. The obtained results indicated that initial teacher trainees found meaning from self-knowledge based on the connection to personal resources and by identifying themselves as unique, worthful people, so they could achieve a personal and professional mission based on their future prospections in addition to goals and even challenges faced along the diverse aspects of their lives. As a conclusion, reaching a connection with meaning of life helps teachers to improve self-motivation and wellness to enjoy a full life that allows them to configure a meaningful daily acting throughout their training journey developing positive attitudes and decision-making skills, embracing responsibilities while successfully perform academic and personal activities by displaying their own potential.